The Impact Of Live Streaming On The Tik Tok Platform On Consumers Impulse To Buy Halal Cosmetic - Amalia As’adi, Firda Rizqi; Frizky, Mochammad Yulian; Chesta Adabi, Muhammad Akmal; Naufanda, Abiyyu Raafi; Nirmala, Ayuni Setiya; Susilowati, Fitriah Dwi; Ramdani (Journal of social Philantrophy and Halal Research, 2024)
Tiktok Live Streaming is one of the features for users who can make Tiktok Live Streaming a promotional medium with creativity in the form of short videos that can be tailored to business needs, so this study aims to determine how Tiktok Live Streaming affects impulse buying for consumers. This research uses quantitative methods, with the use of parametric inferential statistical data analysis techniques. Next, the data is in the form of a questionnaire that is distributed directly. The population in this study were State University students in Surabaya. The sample used was 150 students. Data sources are obtained from primary data where data is taken directly from respondents, namely through filling out questionnaires.